2023
DOI: 10.1101/2023.01.08.23284316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tryptophan metabolism determines outcome in tuberculous meningitis: a targeted metabolomic analysis

Abstract: BackgroundCellular metabolism is critical for the host immune function against pathogens, and metabolomic analysis may help understand the characteristic immunopathology of tuberculosis. We performed targeted metabolomic analyses in a large cohort of patients with tuberculous meningitis (TBM), the most severe manifestation of tuberculosis, focusing on tryptophan metabolism.MethodsWe studied 1069 Indonesian and Vietnamese adults with TBM (26.6% HIV-positive), 54 non-infectious controls, 50 with bacterial mening… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Indeed, increased tryptophan catabolism in the CNS of persons with TBM has been associated with increased survival. (13,14) We observe significantly elevated Th1 (IL-2, IFNg), Th2 (IL-4) and Th17 (IL-17, IL-6, TNFa) effector cytokines in the CSF of persons with TBM, (31) and these cytokines were correlated with CSF concentrations of kynurenine and kynurenic acid. This indicates tryptophan catabolism represents a counter-regulatory process to limit T-cell-mediated inflammation.…”
Section: Tb Meningitis Immunometabolic Networkmentioning
confidence: 72%
See 2 more Smart Citations
“…Indeed, increased tryptophan catabolism in the CNS of persons with TBM has been associated with increased survival. (13,14) We observe significantly elevated Th1 (IL-2, IFNg), Th2 (IL-4) and Th17 (IL-17, IL-6, TNFa) effector cytokines in the CSF of persons with TBM, (31) and these cytokines were correlated with CSF concentrations of kynurenine and kynurenic acid. This indicates tryptophan catabolism represents a counter-regulatory process to limit T-cell-mediated inflammation.…”
Section: Tb Meningitis Immunometabolic Networkmentioning
confidence: 72%
“…While increased CSF concentrations of proinflammatory cytokines IL-1b, TNFa, IL-6, and IFNg are associated with greater disease severity at diagnosis, studies to date have yielded conflicting results about their impact on long-term morbidity and mortality. (8,10,11) Some of this variability may be due to differences in host genetic (12) and metabolic factors (13,14), which have generally gone unmeasured in studies of TBM. Indeed, differences in tryptophan and eicosanoid metabolism are the only host response pathways shown to impact TBM mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speci cally, pyrazinamide-containing regimens had signi cantly lower intracerebral in ammation. High CSF tryptophan levels are associated with increased mortality in patients with TB meningitis 42 , and CSF and plasma tryptophan levels were lower in mice treated with the optimized regimens. Similarly, elevated levels of brain injury markers [GFAP, NEFL (or N ), Tau and S100B] in the CSF or plasma, are associated with poor outcomes in patients with brain damage 43 , and in TB meningitis 44 , and brain injury marker levels in CSF and plasma were lower in mice treated with the optimized regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Immune responses in TBM are thought to be compartmentalized within the central nervous system. Studies have shown that immune cell counts, cytokine concentrations, metabolites and transcriptional responses differ between the peripheral blood and the cerebrospinal fluid (CSF) 10,12,13 . In adults with TBM, leukocyte activation is higher in the CSF than in peripheral blood, although a marked myeloid response in peripheral blood has been reported 10 .…”
Section: Introductionmentioning
confidence: 99%